Charles Munch conducts Wagner, Franck and Fauré - Wagner, Richard 1813-1883; Franck, César 1822-1890; Fauré, Gabriel 1845-1924 (Boston Symphony Orchestra, 2011)
Between 1955 and 1979, Boston's public television station WGBH televised more than one hundred and fifty live concerts by the Boston Symphony Orchestra. Four music directors were featured in the series --
Keywords: Operas; Orchestral music; Suites (Orchestra); Symphonies; Operas -- Excerpts; Internet videos